Possible heart failure caused by osimertinib in a lung cancer patient. (June 2023) - Ruiz-Briones, Paula; Escudero-Vilaplana, Vicente; Collado-Borrell, Roberto; Vicente-Valor, Juan; Alvarez, Rosa; Villanueva-Bueno, Cristina; Narrillos-Moraza, Álvaro; Herranz, Ana; Sanjurjo, Maria
Introduction: Osimertinib is a third-generation tyrosine kinase inhibitor (TKI) indicated for the treatment of epidermal growth factor receptor mutated non-small cell lung cancer (NSCLC). It has demonstrated better results concerning effectiveness than other TKIs for the same indication. However, despite a good safety profile, it could produce some cardiotoxicity that does not occur with other drugs of the same group. Case report: We report the evolution and management of a female patient diagnosed with NSCLC who developed a grade 3 cardiotoxicity due to treatment with osimertinib. This patient suffered from a left bundle branch block, dyslipidemia, and hypertension as cardiovascular risk factors. After a long period of treatment with osimertinib, she developed a severe heart failure (HF) with an important decrease in left ventricular ejection fraction (LVEF), which triggered an admission to the oncology unit for eight days. Management and outcomes: Treatment with osimertinib was first suspended and then resumed after stabilization of the HF. She also developed atrial fibrillation during admission and has required narrow cardiac monitoring and management since the debut of the HF. After evaluating the benefit-risk balance, osimertinib was reintroduced and the patient continues in treatment at the moment, although the baseline LVEF is not recovered. Discussion: There is scarce evidence in the literature concerning HF and important LVEF decrease due to osimertinib. However, its severity and repercussion for the patient justify the thorough screening of cardiovascular risk factors before starting the therapy.